Quantitative Structure-Activity Relationship Analysis of Antimalarial Compound of Mangostin Derivatives Using Regression Linear Approach - Hadanu, Ruslin; Syamsudin (Asian Journal of Chemistry, 2013)
Quantitative electronic structure-activity relationship (QSAR) analysis of a series of mangostin derivatives as antiplasmodial compounds have been conducted using atomic net charges (q), dipole moment (μ) ELUMO, EHOMO, polarizability (a), log P and massa molecular as the descriptors. The descriptors were obtained from computational chemistry method using semi-empirical PM3. Antiplasmodial activities were taken as the activity of the drugs against chloroquine-resistant plasmodiumfalciparum FCR3 strain and are presented as the value of ln (1/IC50) where IC50 is an effective concentration inhibiting 50 % of the parasite growth. The best model of QSAR model was determined by multiple linear regression method and giving equation of QSAR: ln 1/IC50 = -189.029-(752.054) qC5 + (1249.672)qO6 + (3134.359) qC9 + (1174.323) qC10 + (329.121)qC13 - (1.409)μ + (75.214) ELUMO - (23.683) ELUMO - (2.156) a- (3.372) log P + (0.309) MM. The equation was significant on the 95 % level with statistical parameters: n = 15; r = 0.951; r2 = 0.905; SE = 1.326498; Fcalc/Ftable = 1.029 and gave the PRESS = 5.650972. Its means that there were only a relatively few deviations between the experimental and theoretical data of antimalarial activity.